Exploring the teaching of English syntax: tree diagram via an interactive multimedia Computer-aided Learning Material (CALM) / Nor Syahiza Shahabani - Shahabani, Nor Syahiza (2023)
Syntax skills are very important for English language acquisition that enable all English users, especially the Second language learners to improve their writing and speaking skills as the knowledge acquired can guide the users to correctly place the words, phrases and clauses in sentences. Without the knowledge, sentences may not be accurately constructed. Unfortunately, syntax skills and the rules are deemed complicated to learn and acquire. The learning is considered complex that the content is difficult to understand; and also, is acknowledged as boring and not motivating. It negatively affects learners’ English language performance, motivation and attitude. Hence, there is a need to seek better improved teaching and learning materials that can effectively assist syntax learning amongst the Second language learners. One of the learning efforts that can be put forth is by integrating computer technology in the teaching and learning. In this study, mixed-method approach is used. The respondents understudy are the Second language learners; UiTM undergraduate students, taking LG240 (English for Professional Communication) programme. For the purpose of the study, the respondents are divided into experimental and control groups; and, the syntax learning material that is CALM (Computer-aided Learning Material) is developed. The CALM development takes into consideration of the Instructional System Design (ISD) models, motivational consideration that is the ARCS model and the learning theories that are the Behavioural, Cognitivist and Constructivist. Pre-test and Post-test are conducted during the research process in order to determine significant research findings. The respondents also respond to Likert-scale survey questionnaire that is the close-ended survey as well as to open-ended survey and written reflections. The study applies SPSS version 26 for the statistical analysis, and thematic coding is used for the open-ended survey and the reflections. The results of the findings showed that the learning of syntax via media materials improve significantly Second language learners’ performance, motivation, attitude and learning retention. The experimental group outperformed the control group for all the variables tested. From this study, it is hoped that the results and the discussion presented would assist language instructors, content developers, language experts, academicians and all related agencies to incorporate media materials in teaching English syntax, thus, further enrich the L2 language acquisition. This nature of teaching and learning approach can potentially act as a learning alternative to the learners and can provide learning options for better learning. Hence, there is a need to work on such promising learning material with the support of the ISD and motivational models as well as the learning theories. The up-to-date implementation for the syntax learning material that involves computer technology perhaps can be better developed, improved and customised over time.